TINJAUAN MASLAHAH MURSALAH TERHADAP TRADISI UPACARA BESAMPU ANAK BARU LAHIR DI MASYARAKAT KANTU' SANGGAU - Octaviani, Tri Indah; Bakar, Abu; Widiyawati, Ari (Al-Usroh, 2024)
This study aims to: 1) explore the practice of the besampu ceremony tradition for newborns in the Kantu' Sanggau community; and 2) examine the maslahah mursalah related to the besampu ceremony tradition for newborns in the Kantu' Sanggau community. This research employed a qualitative method with a field study design. Primary data were collected through interviews, observations, and documentations. Secondary data were obtained from documents owned by the community members who performed the besampu tradition. Data collection methods included interviews, documentations, and observations. Data analysis techniques involved data reduction, data presentation, and conclusion formulation. Data validity was verified through member checks on all data and information. Based on the analysis, the researcher concluded that: 1) The besampu tradition is a ceremony involving the smoking of a child with a fragrant aroma, aiming for the child to have a better life. 2) The besampu tradition falls under the category of tahsiniyyah maslahah mursalah, as a complement that if not fulfilled, will not cause difficulties, but there is a traditional belief that gives rise to syncretism.